CURRICULUM INNOVATION OF AUSTRALIAN AMEP-CERTIFICATE IN SPOKEN AND WRITTEN ENGLISH (CSWE) - Rahmat Yusny (Englisia: Journal of Language, Education, and Humanities, 2014)
This paper is aimed to analyse Certificate in Spoken and Written English (CSWE) curriculum framework which is currently implemented for Adult Migrant English Pro-gram (AMEP) in Australia. The Curriculum framework that I presented in this writing has been implemented in Australia for more than two decades and has been re-searched and evaluated in delivering better output in order to foster better national economic development in the long run through English, job-seeking, and workplace skills courses. The analysis includes brief history of the curriculum, issues that have been resolved in the implementation and how modern sociolinguistic theories related to social-driven educational innovation in second language learning curriculum design has contributed CSWE development to meet the national demands.